Teleconsultation and Teletreatment Protocol to Diagnose and Manage Patients with Benign Paroxysmal Positional Vertigo (BPPV) during the COVID-19 Pandemic - Barreto,Renato Gonzaga (2021)
Abstract Introduction Telehealth consists in the application of technology to provide remote health service. This resource is considered safe and effective and has attracted an exponential interest in the context of the COVID pandemic. Expanded to dizzy patients, it would be able to provide diagnosis and treatment, minimizing the risk of disease transmission. Benign paroxysmal positional vertigo (BPPV) is the most common vestibular disorder. The diagnosis typically rests on the description of the symptoms along with the nystagmus observed at a well-established positional testing. Objectives The aim of the present study was to propose a teleconsultation and teletreatment protocol to manage patients with BPPV during the COVID-19 pandemic. Methods Specialists in the vestibular field met through remote access technologies to discuss the best strategy to manage BPPV patients by teleconsultation and teletreatment system. Additionally, several scientific sources were consulted. Technical issues, patient safety, and clinical assessment were independently analyzed. All relevant information was considered in order to design a clinical protocol to manage BPPV patients in the pandemic context. Results Teleconsultation for BPPV patients requires a double way (video and audio) digital system. An adapted informed consent to follow good clinical practice statements must be considered. The time, trigger and target eye bedside examination (TiTRaTe) protocol has proven to be a valuable first approach. The bow and lean test is the most rational screening maneuver for patients with suspected positional vertigo, followed by most specific maneuvers to diagnostic the sub-variants of BPPV. Conclusion Although with limited evidence, teleconsultation and teletreatment are both reasonable and feasible strategies for the management of patients with BPPV in adverse situations for face-to-face consultation.